Digital Technology and Teacher Professional Development: Challenges and Contradictions in Compulsory Education - Lourdes Montero-Mesa; Fernando Fraga-Varela; Esther Vila-Couñago; Ana Rodríguez-Groba (MDPI AG, 2023)
The aim of this article is to explore the role of teacher professional development (TPD) in relation to two experiences involving digital technology. Both studies were conducted at a single combined primary and secondary school and involved a total of 727 students. The first study consisted of an ex post facto analysis of attempts to improve student perception of the risks associated with inappropriate use of technology, while the second examined the possible benefits of gamified learning on mathematical fluency using a pre-test/post-test approach. The results reveal the lack of TPD in relation to both experiences, with teachers unable to overcome problems related to technology use and risk perception in the first case, and relegated to the role of mere implementers of an automated learning software product in the second. The conclusions highlight the contradiction between the image of technological innovation in schools and the reality of stasis in teaching practice, as well as the need for further research to assess and promote more effective TPD.